The exhibition The memory of the other in the era of the global: when the curatorship condenses extensive research work (REVISTA NODO, 2024)
The curatorial work of Professor Anna Maria Guasch in the exhibition The memory of the other in the era of the global is rooted in her academic and research career. This exhibition, which toured Bogotá, Santiago de Chile and Havana between 2009 and 2011, reflects the approaches of this author with respect to some of her topics of interest, such as interculturality and the impact of globalization on contemporary art. The proposal is framed in a genealogy of “identity exhibitions”, that begun in 2002 with the curatorship of Okwui Enwezor for Documenta 11 in Kassel, which has been reviewed by the curator herself in her theoretical works and publications. The careful list of artists was expanded with each roaming. Professor Guasch considers the selected projects as “memory repositories” and observes transversal features in them, such as their approach to translation and mediation processes with respect to the contemporary infosphere. In this way, the set proposes a specific planetary geography of places and moments in which dialogues occur between the local and the global, generating a more dynamic understanding of identity narratives under the prism of interculturality.
Keywords: Anna Maria Guasch; Contemporary Art; Globalization; Interculturality; Memory; Multiculturalism